Genome-wide characterization of the TALE homeodomain family and the KNOX-BLH interaction network in tomato - Ezura, Kentaro; Nakamura, Akiyoshi; Mitsuda, Nobutaka (Plant molecular biology, 2022)
Key message Comprehensive yeast and protoplast two-hybrid analyses illustrated the protein–protein interaction network of the TALE homeodomain protein family, KNOX and BLH proteins, in tomato leaf and fruit development. KNOTTED-like (KNOX, KN) proteins and BELL1-like (BLH) proteins, which belong to the same TALE homeodomain family, act together by forming KNOX-BLH heterodimer modules. These modules play crucial roles in regulating multiple developmental processes in plants, like organ differentiation. However, despite the increasing knowledge about individual KNOX and BLH functions, a comprehensive view of their functional protein–protein interaction (PPI) network remains elusive in most plants, including tomato ( Solanum lycopersicum ), an important model plant to study fruit and leaf development. Here, we characterized eight tomato KNOX genes ( SlKN1 to SlKN8 ) and fourteen tomato BLH genes ( SlBLH1 to SlBLH14 ) by expression profiling, co-expression analysis, and PPI network analysis using two-hybrid techniques in yeasts (Y2H) and protoplasts (P2H). We identified 75 pairwise KNOX-BLH interactions, including ten novel interactors of SlKN2/TKN2, a primary class I KNOX protein, and nine novel interactors of SlKN5, a primary class II KNOX protein. Based on these data, we classified KNOX-BLH modules into several categories, which made us infer the order and combination of the KNOX-BLH modules involved in differentiation processes in leaf and fruit. Notably, the co-expression and interaction of SlKN5 and fruit preferentially expressing BLH1-clade paralogs (SlBLH5/SlBEL11 and SlBLH7) suggest their important roles in regulating fruit differentiation. Furthermore, in silico modeling of the KNOX-BLH modules, sequence analysis, and P2H assay identified several residues and a linker region potentially influencing the affinity of BLHs to KNOXs within their conserved dimerization domains. Together, these findings provide insights into the regulatory mechanism of KNOX-BLH modules underlying tomato organ differentiation.